Speech culture formation of future teachers of philology as a scientific and pedagogical problem (Pedagogy of Higher and Secondary Education, 2015)
Levchuk D. V. Speech culture formation of future teachers of philology as a scientific and pedagogical problem.The article deals with the problem of speech culture formation of future teachers of philologycal specialities; the concept of the term "culture of speech" has been defined. Attention tothe basic functions of pedagogical speech and educational problems which students face during speech process is drawn.
Keywords: speech culture; language; speech function; future teachers of philologу